Impact and cultural acceptance of the Narrative Exposure Therapy in the aftermath of a natural disaster in Burundi - Crombach, Anselm; Siehl, Sebastian (BioMed Central ; Springer, 2018)
Background: In the aftermath of natural disasters, affected populations are at risk of suffering from trauma-related mental health disorders such as posttraumatic stress disorder (PTSD) or depression. Particularly in poor post-conflict regions, these mental disorders have the potential to impair the ability of individuals to move on with their lives. We aimed to evaluate the feasibility, cultural acceptance, and effect of a trauma-focused psychotherapy, Narrative Exposure Therapy (NET), in the aftermath of a flood disaster in Burundi. Methods: Fifty-one individuals who were living in emergency camps overseen by the Burundian Red Cross in the aftermath of a flood disaster, and who had lost homes and close relatives, were invited to participate in semi-structured diagnostic interviews. Trained Burundian psychology students conducted these interviews, and six sessions of NET were offered to the 15 individuals most affected by trauma-related symptoms. An additional group of psychology students, blind to the treatment conditions, conducted three and 9 months follow-ups with them including also 25 participants who had reported significant but less severe trauma-related symptoms, assessing mental health symptoms, acceptance of NET, stigmatization due to trauma symptoms, and participants’ economic well-being. Results: Between baseline and 9-months post-intervention assessment, symptoms of PTSD (Hedges’ g = 3.44) and depression (Hedges’ g = 1.88) improved significantly within participants who received NET and within those who received no treatment (Hedges’ gPTSD = 2.55; Hedges’ gdepression = 0.72). Furthermore, those who received NET felt less stigmatized by their participation in the intervention than by the trauma-related mental health symptoms they experienced. Overall, participants reported that they would be willing to forego as much as 1 month’s worth of income in exchange for receiving trauma-focused interventions in the months following the disaster. Conclusions: Individuals severely affected by trauma-related mental health symptoms might benefit significantly from NET in the aftermath of natural disasters, while less affected individuals seem to recover spontaneously. Despite significant challenges conducting NET in emergency camps in the aftermath of natural disaster in a post-conflict country, such interventions are feasible, appreciated and might have long-lasting impacts on the lives of survivors if conducted with due respect to participants’ privacy. Trial registration: UKCR2014 , the 19.06.2014, retrospectively registered.
Aus: BMC Psychiatry, 18 (2018), Nr. 233. pp. 1-15. ISSN 1471-244X